2014
DOI: 10.3139/124.110441
|View full text |Cite
|
Sign up to set email alerts
|

A study on empirical systematic for the (d,n) reaction cross sections at 8.6 MeV

Abstract: Recently, many formalizations have been developed to explain some reaction mechanisms such as neutron or proton induced reactions. In this study, (d, n) reaction mechanism was investigated developing the cross-section systematic formula. The (d, n) cross sections at 8.6 MeV deuteron energy have been calculated using these formula for some target nuclei (A = 10∼123). The cross sections calculated are important for the development of fusion reactor technology. Obtained calculation results from the formula have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Tel et al [5] suggested that the empirical cross section formulae including proton inelastic cross section [13][14][15][16] and Coulomb effects of reactions induced by proton can be expressed as follows,…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…Tel et al [5] suggested that the empirical cross section formulae including proton inelastic cross section [13][14][15][16] and Coulomb effects of reactions induced by proton can be expressed as follows,…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…Systematics of cross-sections has a special importance as an additional tool for the cross-section evaluation [1][2][3]. Many studies on systematics of cross-sections have been done in the literature [4][5][6][7][8][9][10][11][12][13][14][15][16]. Formulas obtained from this systematics have been used in the present study for Li and Be target nuclei irradiated with neutrons and alphas.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron and proton distributions of Li and Beisotopes were studied using the new Skyrme-force parameters by Baldik et al [22]. Tel et al [23] made a study of [8][9][10][11][12][13][14][15][16][17][18] Be isotopes using as a neutron multiplier in reactor design using HartreeFock approximation. The calculations of double-differential neutron emission cross sections for 9 Be target nucleus at 14.2 MeV neutron energy has been investigated by Ş ahan et al [24].…”
Section: Introductionmentioning
confidence: 99%
“…There are many empirical systematics in predicting the neutron induced reaction cross sections of whereas there are very few for proton reactions in literature. Further investigations on various target nuclei at different incident energies are required for performing complete description of the protoninduced reactions [8,12,13]. Data on the excitation function of proton-induced reactions are needed to understand the nature of nuclear interaction and structure.…”
Section: Introductionmentioning
confidence: 99%